Pengaruh Inflasi, Investasi Asing, Pajak Pertambahan Nilai dan Pajak Penghasilan Terhadap Pertumbuhan Ekonomi di Indonesia - Liansyah Pratama; Puti Andiny; Yani Rizal; Safuridar Safuridar (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This study aims to analyze the effect of inflation, foreign investment (PMA), value added tax (VAT), and income tax (PPh) on economic growth in Indonesia in the period 2009-2023. Using quantitative methods and multiple linear regression analysis, secondary data taken from the APBN and BPS portals were processed using Eviews 10. The results of the study indicate that inflation, foreign investment, VAT, and PPh partially do not have a significant effect on economic growth. This study reveals that although fiscal and monetary policies play an important role in economic stabilization, external factors such as the COVID-19 pandemic and global economic dynamics also have a major impact. The implications of this study highlight the importance of institutional and regulatory improvements to maximize the contribution of foreign investment and taxation policies to economic growth.